Corm damage caused by banana weevils Cosmopolites sordidus (Germar) collected from different banana growing regions in Uganda - Twesigye, C.K.; Ssekatawa, K.; Kiggundu, A.; Tushemereirwe, Wilberforce K.; Matovu, E.; Karamura, E.B. (Springer, 2018)
In this study, both healthy tissue culture plantlets and maiden suckers of the Nakitembe cultivar were used to assess the damage level variation caused by banana weevils collected from different banana growing regions. Seventy-nine (79) tissue culture plantlets and fifty (50) suckers were established in buckets in a randomized complete block design for 5 months. Ten adult weevils (5 females and 5 males) were introduced at the base of each plant, and the buckets were covered with a weevil proof mesh. Weevil damage was estimated as a percentage at 60 days after the weevil introduction by estimating the peripheral damage (PD), total cross section corm damage (XT ) and above the collar damage (ACD).